Pernikahan Politik Indonesia (Studi Kasus Pernikahan Adik Jokowi dan Ketua Mahkamah Konstitusi) - Purnama Ayu Rizky (Politicos: Jurnal Politik Dan Pemerintahan, 2022)
Political marriage is a practice that can be traced to its history since the era of the Javanese Hindu kingdom. This practice continues in the current period and is carried out by political elites from local to national levels, from the executive to the judiciary. In the latest case, a political marriage was carried out by the Chief Justice of the Constitutional Court, Anwar Usman and the younger brother of Indonesian President Jokowi, Idayati, on March 26, 2022. This research found that the political marriage showed similarities in patterns, motives, and goals with political marriages that had occurred before, namely to perpetuate the status quo, secure power, and seek allies. This descriptive qualitative research results align with the theory of power relations and knowledge presented by the philosopher Michel Foucault. That power in political marriages has an estuary to perpetuate these relations, strengthen, or isolate them from other power relations. However, in the discipline of Communication and Politics itself, research on political marriage is still rarely carried out in Indonesia. Therefore, this research is essential to fill this gap.